Sistem Monitoring dan Kontrol Tanaman Jeruk Siam Banjar Berbasis IoT Menggunakan Fuzzy Logic Control - Alkaff, Muhammad; Fajar Zulkarnain, Andry; Iqbal Rizqi, Muhammad (IT Journal Research and Development, 2022)
South Kalimantan is one of the largest citrus fruit producers in Indonesia. One of the leading citrus fruit commodities in South Kalimantan is the Siam Banjar oranges (Citrus reticulata). This study developed a monitoring and control system for Siam Banjar orange plants based on IoT (Internet of Things) and Fuzzy Logic Control. The goal is to determine the performance of the Fuzzy Logic Control method in predicting the time to water plants based on temperature and soil moisture. The prototype comprises a Wemos D1 R1 microcontroller with DHT22 and an FC-28 moisture sensor. Two input parameters, temperature and soil moisture are utilised in Fuzzy Logic Control calculations. The output is the duration of the watering time in seconds. During testing, the value of the sensor is compared to existing manual instruments. In addition, fuzzy MatLab calculations are compared to the Fuzzy Logic Control method calculations. The FC-28 Soil Moisture sensor and hygrometer had an error rate of 3.2%, while the DHT22 sensor and thermometer had 1%. The Fuzzy Logic Control test for watering using fuzzy calculations in MatLab yielded a 3 per cent error rate.